A Second-Order ΣΔ ADC Using Sputtered IGZO TFTs - Correia, Ana Paula Pinto; Cândido Barquinha, Pedro Miguel; Goes, João Carlos da Palma; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book discusses the design, electrical simulation and layout of a 2nd-order ∑∆ analog-to-digital converter (ADC), using oxide thin-film transistors (TFTs) technology. The authors provide a unified view of materials science and electronics engineering, in order to guide readers from both fields through key topics. To accomplish this goal, background regarding materials, device physics, characterization techniques, circuit design and layout is given together with a detailed discussion of experimental data. The final simulation results clearly demonstrate the potential of the proposed circuit-level techniques, which enables the implementation of robust and energy efficient ADCs based on oxide TFTs, for moderate resolutions and conversion-rates. Combines materials science and electronics engineering in the same book, making it possible to obtain a general overview, from TFTs production and characterization to their integration in relatively complex circuits; Adapts an a-Si:H TFT RPI model to simulate the behavior of these devices with good fitting to experimental data; Describes the implementation of a 2nd-order ∑∆ ADC using oxide TFTs.
Introduction -- Thin-film transistors -- Oxide TFTs @ FCT-UNL -- Analog-to-digital converters -- A 2nd-order ∑∆ ADC with oxide TFTs @ FCT-UNL -- Conclusions and Future Perspectives.-.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation